(untitled) (diségno, 2023)
Who has not felt the evocation of an architecture or a territory seen from above when looking at a painting by Piet Mondrian? Who has not even seen this reflection written in the many essays that have been developed around his work? It seems to be a biunivocal relationship, in which the observer does not necessarily have to be a skilled architect, or even have any knowledge of architecture. [read more]